RESIDENTIAL OWNERSHIP FOR FOREIGN EMPLOYEES DOMICILED IN INDONESIA - Lalu Husni; Idrus Abdullah; R R. Cahyowati; Any Suryani (NOTARIIL Jurnal Kenotariatan, 2019)
The aims of this research is to examine and analyze: the reasons for justifying the policies issued by the government on residential ownership for foreign employees domiciled in Indonesia, the regulation of residential ownership for foreign employees domiciled in Indonesia, and the procedures of residential ownership for foreign employees domiciled in Indonesia. The method used is legal normative with a statute approach and conceptual approach. Sources and types of legal materials, primary, secondary and tertiary legal materials. The technique of collecting legal materials is done through literature research. The process and analysis of legal materials is carried out in a coherent, and systematic manner, by carrying out classification techniques. As the result, a principle of benefit is the reason for government to issue the policies in which the presence of Foreign employees in Indonesia must beneficial to the national development and not harmful to discipline and security of the Unitary State of the Republic of Indonesia. The regulation started from Indonesian constitution of 1945, Law. No.5 of 1960 concerning Agraria, Law No. 20 of 2011 concerning Flats, Government Regulation No.103 of 2015 concerning Residence Ownership or Occupancy by Foreigners domiciled in Indonesia, Law No.6 of 2011 concerning Immigration and Government Regulation No.26 of 2016 concerning Regulation of Government Regulation No.31 of 2013 concerning Implementation Regulations of Law No. 6 of 2011. The procedures for the ownership of residential houses for Foreign employees domiciled in Indonesia must meet the requirements as stipulated in Government Regulation No.103 of 2015.